Pengaruh Gaya Hidup, Media Sosial, dan Electronic Word of Mouth (E-WoM) Terhadap Keputusan Orang Tua dalam Memilih Lembaga Bimbingan Belajar Anak Hebat (Bimbel AHE) di Yogyakarta - Salsabila, Dila Putri; Prasetyo, Heri; Giyartiningrum, Rr. Eko (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of lifestyle, social media, and electronic word of mouth (E-WoM) on parents' decisions to choose the Tutoring Anak Hebat (Tutoring AHE) institution in Yogyakarta. The research method used is quantitative with data collection using surveys, data quality testing, classical assumption testing, multiple regression analysis testing, and hypothesis testing using SPSS. The population of this study were parents of children studying at Tutoring AHE Yogyakarta with a sample size of 100 respondents. The results of the research show that simultaneously there is a significant influence of lifestyle variables, social media and e-WOM on parents' decisions in choosing the Tutoring institution, but partially the social media variables do not influence parents' decisions in choosing the Tutoring institution in Yogyakarta.